2015
DOI: 10.1109/tgrs.2014.2377293
|View full text |Cite
|
Sign up to set email alerts
|

Focused SAR Image Formation of Moving Targets Based on Doppler Parameter Estimation

Abstract: The present work addresses the problem of focusing moving target in SAR images. This task is here solved by using an Inverse Synthetic Aperture Radar (ISAR) technique. The ISAR technique performs an autofocus procedure by implementing exhaustive search algorithms, improved by classical convex optimization, of functions based on image contrast or entropy. In this work, we discuss the possibility to perform an autofocus ISAR technique by exploiting the estimation of the target Doppler parameters: namely the Dopp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…Since the introduction of synthetic aperture radar (SAR), it has found wide applications in many civilian and military applications due to its ability to generate high-resolution microwave images of observed scenes [1][2][3]. To meet increasing demands, the detection, identification, and tracking of ground-moving targets (GMTs) are of great significance for surveillance systems [4][5][6]. Reports have shown that a long synthetic aperture time is needed to produce a high-quality GMT imaging proposed to generate the image of a ground manoeuvring target by using the SAR technique based on the Hough-generalized high-order ambiguity function (Hough-GHAF).…”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of synthetic aperture radar (SAR), it has found wide applications in many civilian and military applications due to its ability to generate high-resolution microwave images of observed scenes [1][2][3]. To meet increasing demands, the detection, identification, and tracking of ground-moving targets (GMTs) are of great significance for surveillance systems [4][5][6]. Reports have shown that a long synthetic aperture time is needed to produce a high-quality GMT imaging proposed to generate the image of a ground manoeuvring target by using the SAR technique based on the Hough-generalized high-order ambiguity function (Hough-GHAF).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many in‐depth types of researches on the SAR micro‐Doppler effects have been carried out [1–23]. Owing to the micro‐motion characteristics of targets with rotation and vibration, the azimuth echo signals of micro‐motion targets are generally modelled as the form of the sinusoidal frequency modulation (SFM) signal.…”
Section: Introductionmentioning
confidence: 99%
“…The first is range alignment which is coarse compensation [10,11]. The second is phase compensation which compensates the Doppler frequency shift caused by movement [1,5]. Range alignment and phase compensation are also referred to as autofocusing.…”
Section: Introductionmentioning
confidence: 99%